Spinal Cord Injury Current Trends in Acute Management, Function Preservation and Rehabilitation Protocols - Ricciardi, Luca; Lofrese, Giorgio; Perna, Andrea; Trungu, Sokol (IntechOpen, 2023)
Spinal cord injury is a severe scenario that may be caused by traumatic and non-traumatic vertebral or neurological disorders. Neurological impairment, chronic pain, and reduced quality of life may affect patients suffering from spinal cord injury, the onset of which may arise in an acute or chronic manner. Spinal surgeons, anesthetists, neuro-intensivists, neurologists, physiotherapists, rehabilitation medicine doctors, radiologists, neurophysiologists, and carers are all involved in the management of these patients. The chapters in this book combine a useful summary of this topic for non-expert readers with an in-depth study of medical and non-medical experts in the field.